Korea After World War II and the Impact of the Political Change 1948-2007 - et. al., Talal Ismail, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article deals with fundamentals variables after the Second World War, the rise of allies, and the impact on the periphery of states by spreading capitalism and political influence on the Korean Peninsula led by the United States of America, and the emergence of the Republic of Korea as a result of international interactions and the American influence on the political stages of that era in the shadow of a cycle of ups and downs in terms of the rise of political leaders, elites, the army and the civilian opposition, from the period of despotism and dictatorship with the control of the military establishment to the period of democratic transition 1987-1988, to the period of the rise of the opposition and the formation of the first civilian government in the nineties to the rise of the first executive director of Hyundai to the presidency in 2007.